Participatory varietal evaluation and farmer based seed production: a sustainable approach to garlic seed delivery in Atsbi Womberta Wereda, Eastern Tigray - Teweldebrhan, T.G. (Mekelle University, 2009)
Garlic is a newly introduced but potential vegetable crop in the highlands of Tigray. However, there was no information on the agronomic performance of improved garlic varieties and approaches in garlic seed production. Thus, the research was initiated with the objectives to evaluate the performance of improved garlic varieties and to introduce farmer seed production. Ten volunteer garlic seed growers were participated in seed production. Four improved varieties viz Tsedey 92, Bisheftu Netch, G-99-2 and G-161-2 and one local variety Rie local were evaluated under participatory varietal evaluation trial. PVE was conducted on farmers’ field using the randomized complete block design with four replications, taking a farmer as replicate. Significant differences (p<0.05) among varieties were recorded for plant height, number of leaves per plant, leaf length, leaf diameter, total bulb weight, bulb yield per hectare, clove diameter, weight of clove, clove categories, marketable and unmarketable clove, emergence success and days to maturity. Bulb yield per hectare showed positive and significant correlation with most parameters except with medium and small clove categories. This suggested that increment in bulb yield was a result of increase in plant vigor expressed in plant height, number of leaves per plant and leaf diameter. Farmers’ overall evaluation indicated that the varieties Tsedey 92 and Bisheftu Netch were found promising under Atsbi Womberta wereda condition. Farmers, which are participated in the community based garlic seed production improved their availability and access to garlic seed and they also demonstrated and applied how garlic seed production monitored strictly throughout the entire crop growth period, from planting through to harvesting, and storage.